The cholesterol-lowering activity of Averrhoa bilimbi L. leaves ethyl acetate fraction in hypercholesterolemic model - Rahmad Abdillah; Fitra Fauziah; Putri Indah Lestari; Fitri Rachmaini (Universitas Ahmad Dahlan, 2022)
Averrhoa bilimbi L. is used widely as spices and traditional medicine, which contained several chemical compounds such as alkaloid, flavonoid, saponin, and tannin. The aim of this study is to discover the best dose of ethyl acetate fraction from A.bilimbi leaves, which have pharmacology activity on total cholesterol and triglycerides in the hypercholesterolemic model. Thirty adult male white mice were divided into six groups; each group was containing five animals. Five groups were given high-fat diet foods and PTU induced the animals to obtain hypercholesterolemia with a frequency of 1 time a day orally for 14 days, while the normal group was given vehicle (Na CMC 5%) and standard feed. On the 15th day the normal group was given vehicle (Na CMC 5%), negative control group was given high-fat feed, positive control group was given atorvastatin dose 0.26 mg/kg BW, and another group was given ethyl acetate fraction of A.bilimbi leaves dose 200, 400, and 800 mg/kg BW orally. All animal were treated until the 28th day. On day 29, the bloods were taken to determine the total cholesterol and trygliceride levels using clinical photometer 5010 v5+. The data was statistically analyzed using a one-way ANOVA followed by the Duncan Multiple Range Test.. This study indicates that administration of ethyl acetate fraction from A.bilimbi leaves can affect the total cholesterol levels and triglycerides in hypercholesterolemic mice (P<0.05). Ethyl acetate fraction dose 200 mg/kg BW shows the best activity in decreasing total cholesterol levels and triglycerides on mice hypercholesterolemic model (P<0.05).